AB0552 Relative efficacy and tolerability of intravenous and subcutaneous abatacept compared with tumor necrosis factor inhibitors in rheumatoid arthritis patients with an inadequate response to conventional disease-modifying antirheumatic drugs. (23rd January 2014) - Hochberg, M.; Berry, S.; Broglio, K.; Nadkarni, A.; Rosenblatt, L.; Trivedi, D.; Hebden, T.
Abstract : Background: In the absence of direct evidence from randomized clinical trials (RCTs), indirect evaluations such as mixed treatment comparisons use statistical techniques that allow for multiple comparisons to be made across therapies, thus providing clinicians and formulary committee members with information on comparative effectiveness. Objectives: To compare the relative efficacy and tolerability of intravenous (IV) and subcutaneous (SC) abatacept with tumor necrosis factor inhibitors (TNFi) in patients with rheumatoid arthritis (RA) and an inadequate response to disease modifying anti-rheumatic drugs (DMARDs). Methods: A systematic literature review (from 1990-June 2011) identified RCTs of IV and SC abatacept and TNFi (adalimumab, certolizumab, etanercept, golimumab, infliximab) in the DMARD inadequate responders. The five TNFi were combined into a single group for the current analyses and outcomes at 6 months were compared using Bayesian hierarchical models for mixed treatment comparison. Efficacy and safety outcomes of interest included ACR 20/50/70 responses, DAS28 remission and withdrawal due to adverse events (AEs) or due to any reason. Results: Twenty publications describing 15 RCTs were identified. The likelihood of achieving ACR responses at 6 months was comparable between abatacept (both IV and SC) and TNFi: odds ratio [OR] for IV abatacept vs. TNFi for ACR 20 =0.97 [95% confidence interval (CI): 0.74, 1.25], ACR 50, 0.98 [0.73, 1.29], and ACR70, 0.99 [0.68, 1.35], and OR for SC abatacept vs. TNFi for ACR20 =1.05 [0.72, 1.49], ACR50, 1.09 [0.75, 1.51], and ACR70, 1.12 [0.71, 1.64]. The odds of achieving DAS28 remission compared to TNFi were also similar (1.22 [0.74, 1.89] and 1.19 [0.68, 1.95] for IV and SC, respectively). While the odds of withdrawals due to an AE were similar between IV and SC abatacept, the odds were significantly lower for SC abatacept compared to TNFi (0.79 [0.45-1.25] and 0.55 [0.26-0.94] for IV and SC, respectively). Both IV and SC abatacept had a similar likelihood as combined TNFi for withdrawal due to any reason (1.12 [0.61, 1.87] and 1.06 [0.49, 2.02], respectively). Conclusions: After 6 months of therapy, both IV and SC abatacept had similar efficacy compared with TNFi in RA patients with an inadequate response to DMARDs. Compared with TNFi, withdrawal due to an AE were lower for both IV and SC abatacept, this reaching significance for the latter formulation. Disclosure of Interest: M. Hochberg Consultant for: Bristol-Myers Squibb, Abbott Laboratories, Amgen, Genentech/Roche, and UCB Inc., S. Berry Consultant for: Bristol-Myers Squibb, K. Broglio Consultant for: Bristol-Myers Squibb, A. Nadkarni Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, L. Rosenblatt Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, D. Trivedi Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, T. Hebden Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb